Kinetic and kinematic analysis of landing during standing back somersault using three technical arm swings in artistic gymnastics - Mkaouer, B.; Akkari-Ghazouani, H.; Amara, S.; Bouguezzi, R.; Jemni, M.; Chaabene, H. (Journal of Functional Morphology and Kinesiology, 2023)
The crucial criteria when assessing technical performance in artistic gymnastics is the higher elevation of the gymnast`s body and a stable landing (i.e., stick-landing). The purpose of this study was to compare kinetic and kinematic parameters during the landing phase of standing back somersaults (SBS) following three technical arm-swing performed during the preparatory phase in high-level male gymnasts. The three different arm-swing pertain to three "gymnastics schools", i.e., Russian, Chinese, and Romanian. Six high-level male gymnasts participated in this study. Three arm-swing with different angles (i.e., SBS270°, SBS180°, and SBS90°) were randomly performed. A 3D kinetic and kinematic analysis was conducted. Results showed significant variation in the landing angle (p = 0.009) across the three arm-swing techniques. The SBS90° arm-swing resulted in the closest angle to the vertical. Additionally, the SBS90° arm-swing technique induced the lowest horizontal and vertical force values upon landing compared to the other arm-swing techniques (SBS270°: p = 0.023 and 0.009, respectively; SBS180°: p = 0.004 and 0.080, respectively). The same was noted for the horizontal velocity (p = 0.021) with the lowest values noted for the SBS90° arm-swing technique. However, the best opening angle was observed during the SBS270° technique, since it presented the best vertical displacement. In conclusion, the SBS with a SBS90° arm-swing seems to favor a better absorption of the ground reaction force upon landing by reducing the intensity of the impact with the ground and by affording a landing angle closer to the vertical in high-level male gymnasts.